2022
DOI: 10.15585/mmwr.mm7138a3
|View full text |Cite
|
Sign up to set email alerts
|

Notes from the Field: Norovirus Outbreaks Reported Through NoroSTAT — 12 States, August 2012–July 2022

Abstract: Norovirus is the leading cause of acute gastroenteritis in the United States (1). In April 2020, the incidence of norovirus outbreaks in the United States declined substantially, likely because of implementation of COVID-19-related nonpharmaceutical interventions, such as facility closures, social distancing, and increased hand hygiene (2). Similar declines were observed in other countries (3,4). Norovirus outbreaks in the United States increased rapidly starting in January 2022, approaching prepandemic (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…are the major causes of diarrheal diseases and death [6]. Furthermore, norovirus infections are the principal cause of foodborne disease outbreaks and are associated with approximately 20% of diarrhea cases, with similar prevalence in both children and adults [13,14]. Hundreds of millions of people across the globe are estimated to have clinically diagnosable campylobacteriosis and giardiasis annually [15], while cholera continues in disaster-and war-inflicted countries such as Yemen [16], South Sudan [17], and recently Syria and Lebanon [18], with an estimated annual toll of 1.3-4.0 million cases globally [19].…”
Section: Introductionmentioning
confidence: 99%
“…are the major causes of diarrheal diseases and death [6]. Furthermore, norovirus infections are the principal cause of foodborne disease outbreaks and are associated with approximately 20% of diarrhea cases, with similar prevalence in both children and adults [13,14]. Hundreds of millions of people across the globe are estimated to have clinically diagnosable campylobacteriosis and giardiasis annually [15], while cholera continues in disaster-and war-inflicted countries such as Yemen [16], South Sudan [17], and recently Syria and Lebanon [18], with an estimated annual toll of 1.3-4.0 million cases globally [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous norovirus outbreaks have occurred among river rafters in Grand Canyon associated with contaminated food products ( 7 ) and person-to-person transmission ( 8 ) resulting in recommendations to adhere to strict hygiene guidance. An increase in norovirus activity was observed at a national level in spring 2022, with the number of outbreak reports returning to prepandemic levels for the first time since March 2020 ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Norovirus is also the most identified source pathogen among acute gastroenteritis (AGE) outbreaks. 3,4 A review of US AGE outbreaks from 2009-2019 found that 62% were spread primarily by person-to-person contact. 3 Norovirus transmissibility can be reduced by handwashing with soap and water, avoiding food preparation until ≥48 h after symptoms end, and proper cleaning and disinfection of contaminated surfaces.…”
Section: Introductionmentioning
confidence: 99%